Suprainguinal Fascia Iliaca Block and Pericapsular Nerve Group Block Catheter Procedure for Postoperative Joint Motion Limitation Rehabilitation - Taşkın, Öztürk; Demir, Ufuk; Yılmaz, Ayşe; Tanyıldızı Küçük, Büşra; Kütük, Emir; Doğanay, Zahide (Springer Science and Business Media LLC, 2025)
A distal femur fracture is an orthopedic condition that can be seen in all age groups and causes severe pain both preoperatively and postoperatively. Poorly managed pain can lead to hemodynamic changes, the need for additional analgesic drugs containing opioids, increased hospital stay, delayed mobilization, and patient dissatisfaction. Regional anesthesia techniques can be used for preoperative and postoperative analgesia. Suprainguinal fascia iliaca block and pericapsular nerve group block are applications included in regional techniques that preserve motor functions of the thigh. We also share our experience of suprainguinal fascia iliaca block and pericapsular nerve group block catheter application that we applied to a patient who underwent tenolysis surgery due to a distal femur fracture and adhesion in the quadriceps muscle group.
Keywords: Anesthesiology